"If I Can Grapple With This I Can Truly Be Of Use In The Therapy Room": Using The Therapist's Own Emotional Struggles To Facilitate Effective Therapy. (17th December 2012) - Aponte, Harry J.; Kissil, Karni
<x xml:space="preserve">Abstract</x> This study premises that self‐of‐the‐therapist work is pivotal in the development of effective therapists. However, therapy models vary in their goals for this work and the means of accomplishing them. This study presents the perspective of the person‐of‐the‐therapist Training (POTT) model that prioritizes the ability to consciously and purposefully use the self‐as‐is at the moment of contact with the client over the traditional goal of therapists working to resolve their issues. A key underlying assumption of the model proposes that therapists' core issues (referred to as "signature themes") are potent resources that can be tapped into to connect, assess and intervene effectively with clients. The study presents the model and illustrates the use of signature themes in clinical work.